Estrogen Receptor-Positive and Estrogen Receptor-Negative Human Breast Cancer Cells: Regulation of Expression of Cancer-Related Genes by Estradiol and Tamoxifen - Murthy, Ven; Yuan, Xia; Liu, Guojin (Current Signal Transduction Therapy, 2008)
Breast cancer is one of the most prevalent forms of carcinomas among women world-wide. The oncogenes, tumor suppressor genes and antioxidant enzyme genes are cancer-related genes which play an important role in the initiation, metastasis and malignancy of many cancers, including breast cancer. Estrogen which is a key steroid hormone in the regulation and differentiation of the normal breast also appears to be involved in the carcinogenesis of this tissue. Antiestrogen therapy, such as the use of tamoxifen, targets the estrogen receptors (ER) through which estrogen exerts both its normal biological function as well as the molecular processes leading to cancer formation. The objectives of the present study were to characterize and quantify the expression of genes related to human breast carcinogenesis, using ER- positive (ZR-75-1) and ER-negative (MDA-MB-231) cells as in vitro cellular models of breast cancer. We have examined the expression of a number of genes which have an important clinical significance in human breast cancer, when expressed at levels below or above the normal range. Among these are the receptor oncogenes (EGFR, c-erbB2), other oncogenes (pS2, hMAM, MUC1 and CK-19), the tumor suppressor gene, p53, as well as four of the major antioxidant enzyme genes. These are superoxide dismutase-1 (SOD1), superoxide dismutase-2 (SOD2), Se-glutathione peroxidase (GPx1) and catalase (CAT), all of which have been well characterized in human cells, and whose activities have been localized to different cellular compartments, such as the cytoplasm, mitochondria and peroxisomes. Gene expressions were determined using real-time PCR, in control untreated cells as well as when these two cell types were exposed to 17β-estradiol (E), or tamoxifen (TAM) or a combination of E and TAM. Our results show that basal level expressions of receptor oncogenes (EGFR and c-erbB2) as well as two of the four antioxidant enzyme genes (SOD2 and GPx1) were several folds lower in ER-positive breast cancer cells (ZR-75-1) as compared to ER-negative cells (MDAMB- 231). However, treatment with E and TAM, either individually or in combination, produced much greater effects on the ER-positive cells than on the ER-negative cells, with the result that these genes were greatly overexpressed in the ER-positive cells as compared to the ER-negative cells. Of these, the receptor oncogene, c-erbB2, and the antioxidant enzyme gene, SOD2, were the most affected, resulting in striking upregulations ranging over several hundred folds. This, and other observations, would suggest that the carcinogenic effects of estradiol and the anticarcinogenic effects of tamoxifen are not only mediated by the presence of estrogen receptors, but may also be regulated, either directly or indirectly, through other mechanisms, including the mitochondrial antioxidant system.
Keywords: tumor suppressor genes